2003
DOI: 10.1080/713842361
|View full text |Cite
|
Sign up to set email alerts
|

The Politics of Grief and Continuing Bonds With the Dead: The Cases of Maoist China and Wahhabi Islam

Abstract: The article is a contribution to a cross-cultural theory of grief. It examines the relationship between individual/family continuing bonds with the dead and cultural narratives that legitimize political power. The dead are collective representations (Dirkheim) that mediate the larger culture to individuals and to smaller communities and that reinforce social solidarity and identity. The political question is which collective--family, community, church, party, nation--owns the dead and controls the rituals by w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Here we argue that human geography could productively engage in interdisciplinary studies of dead bodies at a range of scales. To begin with, it is important to note the theoretical turn within the discipline of death studies towards the ‘continuing bonds’ model of bereavement (Klass and Goss 2003; Klass et al . 1996), which recognises the importance of people’s continuing attachment to their dead loved ones (in contrast to the ‘broken bonds’ model, which has until recently dominated modern Western societies and bereavement counselling, i.e.…”
Section: Geography ‘Dead Body Politics’ and The Agency Of Corpsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we argue that human geography could productively engage in interdisciplinary studies of dead bodies at a range of scales. To begin with, it is important to note the theoretical turn within the discipline of death studies towards the ‘continuing bonds’ model of bereavement (Klass and Goss 2003; Klass et al . 1996), which recognises the importance of people’s continuing attachment to their dead loved ones (in contrast to the ‘broken bonds’ model, which has until recently dominated modern Western societies and bereavement counselling, i.e.…”
Section: Geography ‘Dead Body Politics’ and The Agency Of Corpsesmentioning
confidence: 99%
“…Death, and corpses, must be understood within the specific socio‐spatial context in which they occur (Connor 1995; Klass and Goss 2003; Maddrell and Sidaway 2010b; Woodthorpe 2010). As Klass and Goss suggest, ‘narratives of grief and continuing bonds at particular times and places need to be understood in terms … of their relationship to cultural narratives that legitimize political power’ (2003, 808).…”
Section: Corpses Dead Body Politics and Agency: Following The Dead Bmentioning
confidence: 99%
“…Instead, bereavement studies are often situated in communities characterized by shared circumstances such as poverty and high mortality (e.g., Scheper-Hughes 1993), or shared religion as shown in studies of bereavement in Muslim majority societies by Klass and Goss (2003) and Suhail et al (2011). Thus, little is known with regard to processes of meaning-making following the death of a loved one among religious minorities in Western societies.…”
Section: Death the Human Condition And The Meaning Of Lossmentioning
confidence: 97%
“…There, traditions value acceptance and facilitate ways of continuing bonds with the deceased, e.g., through prayer, charity and graves visitations (Klass and Goss 2003;Suhail et al 2011). Although religion often lays the foundation for (re)making meaning and establishing order among the bereaved, Islamic rituals are enacted differently as a function of divergent societal contexts.…”
Section: Death the Human Condition And The Meaning Of Lossmentioning
confidence: 98%
“…Silverman and Nickman (1996) have suggested that ''the focus in facilitating mourning may need to be on how to change connection and give the relationship a new perspective rather than on how to separate' ' (p. 86). Establishing these continuing bonds means internalizing the deceased into the self or other mental representations (Klass & Goss,1999;Klass & Goss, 2003;Noppe, 2000;Reisman, 2001;Russac, Steighner & Canto, 2002).…”
mentioning
confidence: 98%